Quantitative assessment of vibrating insole prototype that induced transient comfort among female school teachers - Alias, Ayuni Nabilah (2021)
Introduction: Musculoskeletal disorders (MSDs) are amongst the most significant and common occupational health issues in the teaching profession, which although was long neglected, this female-dominated profession has attracted growing attention in recent years. School teachers were found to be at risk of high prevalence of lower extremity MSDs (LEMSDs) compared to other occupational groups. Along with greater responsibilities, teachers are continually exposed to poor posture in unfit working circumstances during school hours, which contributes to a variety of health concerns. Teachers spend much of their time standing and moving about, often contributing to body pain and discomfort, muscle fatigue and even health problems such as musculoskeletal injuries, most of which involved the lower extremity of the body, especially the feet. Due to this, a vibrating insole prototype was assessed in this study to induce transient comfort among female school teachers. Method: This research was an experimental pre-posttest study (randomized controlled trial) that involved female primary school teachers in Terengganu. In this study, a total of 124 female school teachers were randomly assigned to experimental and control groups based on inclusion and exclusion criteria. Experimental group consisted of 62 teachers, they were asked to wear a shoe attached with a vibrating insole prototype and another 62 teachers in control group were asked to wear a shoe without a vibrating insole prototype attached. The experimental session took place during teaching session in a classroom (the first period in the morning) and each session lasted for one-hour. Every respondent had to attend an experimental session on two separate days, with a minimum interval of three days between the sessions. During the one-hour session, respondents were attached with wireless electromyography (EMG) on the right and left legs’ muscles. The EMG data was collected continuously for one-hour session. They were also needed to evaluate their discomfort level for all body parts in the Borg’s scale CR-10 questionnaire for every 15 minutes until the end of one-hour experimental session. Results: Discomfort rating (Borg’s scale) revealed that, with the presence of the vibrating insole prototype, the ankles and feet showed highest reduction with 67% of discomfort level for the experimental group compared to the other parts of the body. All in all, there were 12% to 67% reductions of discomfort level for all body parts during one-hour prototype testing among female school teachers. Electromyography (EMG) measurements showed that there were 13% to 16% more reductions of exertion of muscle activity (%) for both right and left legs’ muscles for the experimental group compared to the control group during the one-hour prototype testing. The discomfort rating (Borg’s scale) for ankles and feet was substantially lower (p<0.05) in the experimental group relative to the control group from 15 minutes to the end of the experimental testing in the one-hour duration. Lastly, statistical results reported that there were significant exertion changes of muscle activity (EMG) within the one-hour prototype testing, (X2 (15) = 289.94, p<0.001) for the experimental group compared to the control group. Conclusion: Potential use of a vibrating insole prototype has offered valuable ergonomic support that helps to reduce muscle and body discomfort and improve the posture of school teachers with a positive effect on lower leg muscle activity. Therefore, vibrating insole prototype is capable of providing an ideal intervention to the school teachers’ feet and potentially reducing the progression of musculoskeletal disorders in a long-term health effect. Further development of the design specifications is required to make vibrating insole more acceptable to school teachers in order to improve the dynamics of body posture without placing excessive stress on the lower leg, especially the feet during school session. A long-term and high-quality study is needed before definitive conclusions can be drawn on the effect of vibrating insole prototype on comfort and muscle activity with a much wider population and more variations in measurements.